The activist - Grisham, John (Grisham, John. Theodore Boone, 2014)
When Strattenburg is thrown into chaos over a political and environmental debate, Theodore Boone finds himself in the middle. Upon discovering corruption disrupting the case, Theo must risk his own life and the safety of his loved ones to stand up for what he believes in.